Electric Field Analysis of Breast Tumor Cells - V. Gowri Sree; K. Udayakumar; R. Sundararajan (International Journal of Breast Cancer)
An attractive alternative treatment for malignant tumors that are refractive to conventional therapies, such as surgery, radiation, and chemotherapy, is electrical-pulse-mediated drug delivery. Electric field distribution of tissue/tumor is important for effective treatment of tissues. This paper deals with the electric field distribution study of a tissue model using MAXWELL 3D Simulator. Our results indicate that tumor tissue had lower electric field strength compared to normal cells, which makes them susceptible to electrical-pulse-mediated drug delivery. This difference could be due to the altered properties of tumor cells compared to normal cells, and our results corroborate this.